(untitled) (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the outcome of posterior interosseous artery (PIA) flap in terms of coverage of the defects and survival of the flap in patients with complex defects over the dorsum of hand and distal forearm. Methods: This descriptive study was conducted in Hand and Upper Limb Surgery (HULS) CMH Lahore Medical College, Lahore, Pakistan from 15th July 2017 to 15th August 2019.All patients with complex defects of the dorsum of the hand and distal forearm were treated with posterior interosseous artery (PIA) flap. Post operatively the grafts were observed for coverage of the defects and graft survival. Results: The total number of patients were 24 with 19(79.1%) males and 05(20.8%) females. The mean age was 37±7SD(range 21 to 56 years). Right hand was involved in 17(70.8%) patients and left in 7(29.1%) patients. Complete coverage of the defects were achieved in all cases. Successful graft survival and uptake was seen in 20(83.3%) flaps. Partial loss was seen in 03 (12.5%) flaps which required debridement and subsequent Split Thickness Skin Grafting. Complete graft loss was seen in 01 (4.1%) flap Conclusion: Posterior interosseous artery flap (PIA) had higher survival rates and larger area of the dorsum of the hand and distal forearm were entirely covered with this graft. We recommend posterior interosseous artery flap as first line surgical technique to treat complex tissue defects of the dorsum of the hand and distal forearm.